2000
DOI: 10.4049/jimmunol.164.5.2790
|View full text |Cite
|
Sign up to set email alerts
|

Naturally Developing Memory T Cell Xenoreactivity to Swine Antigens in Human Peripheral Blood Lymphocytes

Abstract: Naturally developing xenospecific Abs are well-documented barriers to xenograft transplantation in humans, but whether analogous xenoreactive T cell immunity develops is not known. We used an enzyme-linked immunospot assay to determine the frequency and cytokine profiles of xenoreactive PBLs from a panel of human volunteers. Because naive T cells produce only IL-2 in short term culture, IFN-γ production by this approach is a measure of a memory immune response. Stimulation of human PBLs or purified T lymphocyt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0

Year Published

2001
2001
2008
2008

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 28 publications
2
18
0
Order By: Relevance
“…Allo-reactive memory T cells are reported as important mediators in acute rejection, jeopardizing the survival of transplanted allo-grafts (1,2). The questions remain to be answered as to when and how naive T cells develop into effector and specific memory T cells immediate after alloantigen encountering.…”
Section: Introductionmentioning
confidence: 99%
“…Allo-reactive memory T cells are reported as important mediators in acute rejection, jeopardizing the survival of transplanted allo-grafts (1,2). The questions remain to be answered as to when and how naive T cells develop into effector and specific memory T cells immediate after alloantigen encountering.…”
Section: Introductionmentioning
confidence: 99%
“…To investigate whether naive mice possessed anti-porcine effector memory T cells, we used a recall (20-h) ELISPOT assay with IFN-␥ secretion as readout. Such assays have been shown to detect the presence of effector memory T cells in both mice and humans (32). The results show that spleen cells from naive aly/aly mice failed to demonstrate an increase in the frequency of IFN-␥-positive cells when exposed to mitomycin C-treated porcine spleen cells in a one-way MLR vs naive aly/aly responders only (exposed aly/aly spleen cells ϭ 10 spots/1 ϫ 10 6 spleen cells vs aly/aly responders only ϭ 12 spots/1 ϫ 10 6 spleen cells, p ϭ 0.6) (Fig.…”
Section: No Evidence Of Preformed Abs or Preformed Effector Memory T mentioning
confidence: 99%
“…A characteristic of effector memory T cells is their ability to rapidly secrete IFN-␥ in response to their cognate Ag (32). To investigate whether naive mice possessed anti-porcine effector memory T cells, we used a recall (20-h) ELISPOT assay with IFN-␥ secretion as readout.…”
Section: No Evidence Of Preformed Abs or Preformed Effector Memory T mentioning
confidence: 99%
“…We previously made use of this approach to characterize human T cell immunity specific for both prototypic protein antigens (i.e., tetanus toxoid and purified protein derivative), for alloantigens, and for xenoantigens (32,33). These published studies have further demonstrated that our approach can have prognostic value in that the frequency of donor antigen-specific T cells, as defined by ELISPOT assay, can predict those renal transplant recipients at highest risk for rejection episodes (33).…”
Section: Hepatitis C Virus (Hcv)mentioning
confidence: 99%
“…After obtaining consent, 30-cc peripheral blood samples were obtained in green-top vacutainer tubes containing sodium heparin. PBLs were isolated by centrifugation through Isoprep (Robbins Scientific Corp., Sunnyvale, CA) within 4 h of obtaining the sample, as previously described (32,33). A quantity of 20 -40 million PBLs was obtained from a given patient by this method.…”
Section: Patient Populationmentioning
confidence: 99%